Biological Determinants of Memory Performance In Qur’an Memorizers: Evidence from Cathecol-O-Methyl-Transferase (COMT) Gene Expression And Protein Levels - Rosdianah Rahim; Suryani As’ad; Veni Hadju; Saidah Syamsuddin; Muhammad Hatta; Nadyah Haruna; Syatirah Jalaluddin; Yessy Kurniati (Biology, Medicine, & Natural Product Chemistry, 2026)
Memory performance during adolescence is a key aspect of cognitive development and is strongly influenced by dopaminergic regulation in the prefrontal cortex. Catechol-O-Methyltransferase (COMT) plays a critical role in modulating dopamine availability and cognitive function. This study examined the relationships between age, COMT gene expression, COMT protein levels, and memory performance among adolescents engaged in structured memorization activities. A quantitative cross-sectional design was applied involving male adolescent participants. Memory performance was assessed using a standardized psychometric test, while COMT gene expression and protein levels were measured using reverse transcription quantitative polymerase chain reaction and enzyme-linked immunosorbent assay, respectively. Statistical analyses included descriptive statistics and correlation tests. The results demonstrated a significant negative association between age and memory performance within the adolescent range. In contrast, COMT gene expression and protein levels showed strong positive correlations with memory performance, indicating that higher molecular regulation of dopamine was associated with superior cognitive outcomes. Memorization duration and quantity were not significantly related to memory performance. These findings support dopamine-based models of cognitive regulation and highlight the importance of molecular biomarkers in understanding adolescent memory development. The study contributes to developmental cognitive research by emphasizing biologically informed approaches and provides a foundation for future longitudinal investigations.